2022
DOI: 10.1093/nar/gkac1130
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor c-Jun inhibits RBM39 to reprogram pre-mRNA splicing during genotoxic stress

Abstract: Genotoxic agents, that are used in cancer therapy, elicit the reprogramming of the transcriptome of cancer cells. These changes reflect the cellular response to stress and underlie some of the mechanisms leading to drug resistance. Here, we profiled genome-wide changes in pre-mRNA splicing induced by cisplatin in breast cancer cells. Among the set of cisplatin-induced alternative splicing events we focused on COASY, a gene encoding a mitochondrial enzyme involved in coenzyme A biosynthesis. Treatment with cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Cisplatin is a DNA-crosslinking anticancer agent that is widely used in non-small cell lung cancer (NSCLC) treatment (22). It widely regulates alternative splicing (23, 24) but little is known about its effects on IPA isoforms. In this study, by investigating on IPA isoform regulation by cisplatin in NSCLC cells, we identified cisplatin-regulated IPA isoforms that terminate within the annotated 5’UTR part of genes, encode microproteins, and impact cell response to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is a DNA-crosslinking anticancer agent that is widely used in non-small cell lung cancer (NSCLC) treatment (22). It widely regulates alternative splicing (23, 24) but little is known about its effects on IPA isoforms. In this study, by investigating on IPA isoform regulation by cisplatin in NSCLC cells, we identified cisplatin-regulated IPA isoforms that terminate within the annotated 5’UTR part of genes, encode microproteins, and impact cell response to cisplatin.…”
Section: Introductionmentioning
confidence: 99%